Features of the risks analysis in information and communications systems - Архипов, Александр Евгеньевич (Ukrainian Information Security Research Journal, 2012)
The basic properties of the information and communication systems (ICS), and the definition of the term ICS are considered. It is shown that for modern ICS, the basis of industrial and organizational management activity of which is a business process, is characterized by variability of the structure and composition of the threat model, the final time of the threats existence, change of the threat realization probability in the limit of time its existence. The necessity of the process define of the probability properties of threats realization of the information in ICS and dynamic characteristics of the threats risks are proved. The concepts of the terminal probability and methods of its calculation are introduced. The latest are presented by the script method of the determining of the values of the terminal probability and by the expert method in which implemented the ability to update previously received expert estimates using the addition of new incoming information.